2022
DOI: 10.1161/circimaging.122.014645
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Echocardiographic Parameters to Improve the Diagnostic Yield of Tc-99m-Bone Avid Tracer Cardiac Scintigraphy for Transthyretin Cardiac Amyloidosis

Abstract: Background: Echocardiographic deformation-based ratios and novel multi-parametric scores have been suggested to discriminate transthyretin cardiac amyloidosis (ATTR-CM) from other causes of increased left ventricular wall thickness among patients referred for ATTR-CM evaluation. Their relative predictive accuracy has not been well studied. We sought to (1) identify echocardiographic parameters predictive of ATTR-CM and (2) compare the diagnostic accuracy of these parameters in patients with suspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…14,15,32,33 Furthermore, by using twodimensional speckle tracking techniques, "apical sparing" in LV contraction has been found to be related to CA. 25,[34][35][36][37] In our study, these two factors were selected as discriminators of 99m Tc-PYP scintigraphy-positive cardiomyopathy, which was in concordance with those previous reports.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…14,15,32,33 Furthermore, by using twodimensional speckle tracking techniques, "apical sparing" in LV contraction has been found to be related to CA. 25,[34][35][36][37] In our study, these two factors were selected as discriminators of 99m Tc-PYP scintigraphy-positive cardiomyopathy, which was in concordance with those previous reports.…”
Section: Discussionsupporting
confidence: 89%
“…In recent years, LV wall thickness has been thought to be the most practical and reliable two‐dimensional echocardiographic measure to identify cardiac amyloidosis (CA) 14,15,32,33 . Furthermore, by using two‐dimensional speckle tracking techniques, “apical sparing” in LV contraction has been found to be related to CA 25,34–37 . In our study, these two factors were selected as discriminators of 99m Tc‐PYP scintigraphy‐positive cardiomyopathy, which was in concordance with those previous reports.…”
Section: Discussionsupporting
confidence: 89%
“…Of note, a recent study evaluating the role of echo parameters in predicting PYP scan positivity showed similar findings. In this study inferolateral (posterior) wall thickness >14 mm along with basal longitudinal strain were the best predictors of PYP positivity [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since ATTR-CM and HFpEF have overlapping clinical features, the identification of the ATTR-CM burden in HFpEF patients remains challenging. Recently, several scoring systems based on echocardiography or electrocardiography have been developed to detect cardiac amyloidosis 31,32 or a specific ATTR-CM subtype, [33][34][35] such as the AL score, 31 Increased Wall Thickness (IWT) score, 31,35 AMYLI score, 32 strain-based ratios 33 and the RWT/SavR index (Table S4). 34 Similarly, Sperry et al demonstrated that patients with an echocardiographic phenotype of s' velocity ≤6 cm/s and IVS ≥12 mm in the TOPCAT study were more likely to be cardiac amyloidosis, associated with poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, it failed to distinguish ATTR-CM from light-chain amyloidosis. 12 The strain-based ratios 33 and the RWT/ SavR index 34 were mainly derived from patients with clinically suspected ATTR-CM regardless of the presence of HFpEF, whereas the IWT score (≥8 points) performed well with a sensitivity of 85.7% and a specificity of 92.6% for ATTR-CM identification in a Chinese HFpEF cohort. 35 However, the ATTR-CM burden as detected by an IWT score ≥8 was only 5.3%, possibly due to the racial disparities, lack of external validation design and the low proportion of patients undergoing 99m Tc-PYP (only 13.1%).…”
Section: Discussionmentioning
confidence: 99%